Evaluating Vegetable Oils as Eco-Friendly Alternatives in Metal Heat Treatment : Review - sukendar, Sukendar; Alva, Sagir; Ginting, Dianta (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2026)
Recent research on sustainable heat-treatment processes highlights the strong potential of vegetable oils as environmentally benign quenching media. This review integrates thermo-physical characteristics, cooling behavior, and mechanical performance reported in key studies from 2010–2024. Vegetable oils demonstrate higher quenching severity (H-value 0.17–0.21) than mineral oils (0.11–0.14), supported by stable viscosity ranges (20.78–110.35 cSt at 40°C; 6.9–33.65 cSt at 100°C) and superior thermal conductivity (0.131–0.182 W/m°C) relative to SAE40 (0.145 W/m°C). Their mechanical performance is consistently favorable: palm kernel oil yields hardness up to 40.85 HRC, cottonseed oil ~33.25 HRC, and groundnut oil produces ~173.8 HV with yield strength reaching 805 MPa. Neem seed oil exhibits exceptional hardness (68.7 HRA) and tensile strength (2122 MPa), while marula oil significantly enhances the hardness and tensile strength of medium-carbon steels. Soybean, sunflower, and canola oils applied to AISI 1045 steel deliver hardness levels of 41–50 HRC. Impact toughness also improves, with neem oil reaching 15 J and additive-modified quenchants containing 5% metal salts achieving up to 131 J. Antioxidant-fortified oils (Irganox L109, TBHQ, Propyl Gallate) further improve oxidation resistance without impairing cooling performance. Overall, properly stabilized vegetable oils represent robust, efficient, and environmentally responsible quenching alternatives for the heat treatment of low- and medium-carbon steels.